2001
DOI: 10.1046/j.1365-2435.2001.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in thermal tolerance among natural populations of Drosophila buzzatii: down regulation of Hsp70 expression and variation in heat stress resistance traits

Abstract: Summary1. Thermal adaptation was investigated in the fruitfly Drosophila buzzatii Patterson and Wheeler. Two natural populations originating from a high-and a low-temperature environment, respectively, were compared with respect to Hsp70 (heat shock protein) expression, knock-down resistance and heat shock resistance. 2. Three main hypotheses were tested: (i) The expression level of Hsp70 in flies from the high-temperature habitat should be down-regulated relative to flies from the colder habitat. (ii) Flies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
250
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(284 citation statements)
references
References 34 publications
32
250
1
1
Order By: Relevance
“…However, HSP expression might also incur fitness costs on individuals that regularly experience environmental stress, because of the reduced energy available for growth and reproduction, suggesting that evolution in harsh environments will result in selection for reduced HSP expression. This position is supported by our recent study in Sphincterochila snails and by studies in other organisms; for example, in natural populations of Drosophila from different climates (Sørensen et al, 2001) and in marine snail Tegula species of different biogeographical ranges (Tomanek and Somero, 2002).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…However, HSP expression might also incur fitness costs on individuals that regularly experience environmental stress, because of the reduced energy available for growth and reproduction, suggesting that evolution in harsh environments will result in selection for reduced HSP expression. This position is supported by our recent study in Sphincterochila snails and by studies in other organisms; for example, in natural populations of Drosophila from different climates (Sørensen et al, 2001) and in marine snail Tegula species of different biogeographical ranges (Tomanek and Somero, 2002).…”
Section: Introductionsupporting
confidence: 61%
“…Thus, because HSP expression might incur fitness costs on individuals that regularly experience environmental stress, evolution in harsh environments might result in selection for reduced HSP expression. Indeed, there are studies demonstrating lower levels of standing stocks of Hsp70 in the more thermally resistant species compared with the heat-sensitive ones Sørensen et al, 2001;Tomanek and Somero, 2002;Zatsepina et al, 2001). Our previous work (Mizrahi et al, 2010) supports this approach, demonstrating lower endogenous levels of Hsp72 in the desiccationresistant S. zonata compared with the desiccation-sensitive S. cariosa.…”
Section: Cost Benefits and Survival Strategymentioning
confidence: 99%
“…Regarding the 6-fold induction, we consider that the experimental materials, which were taken from the northernmost province of China in Heilongjiang Province (Habin, 130°10'N, 46°40'E), may be an important factor. Some studies have shown that production of HSP70 in response to temperature shock is less intense in organisms that are more frequently exposed to unfavorable temperatures in their habitat than in organisms in benign conditions (Sørensen et al 2001;Lyytinen et al 2012). As the synthesis of HSP70s requires considerable energy and may thus occur at the cost of the synthesis of other proteins (Krebs & Loeschcke1994), northern populations might have evolved a less costly way to resist cold stress (Lansing et al 2000;Sørensen et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These constitutively expressed stress proteins have chaperone function in protein folding processes, stabilize proteins in intracellular trafficking, and play an essential role in the assembly, degradation, and intracellular localization of proteins (Fink 1999;Hendrick and Hartl 1993;Mayer and Bukau 2005). It is known that different populations of a species can differ in their Hsp70 content and in their ability to induce Hsp70 as a response to heat, depending on their natural habitat and on the organisms' general ability of Hsp70 induction as, for example, shown in whole body homogenates of Drosophila sp flies (Bahrndorff et al 2006;Krebs and Feder 1997;Sørensen et al 2001). In case of X. derbentina, analyses of whole body homogenates have shown that the Hsp70 level of individuals depends on the population (Di , the life stage, the season, and the intensity of heat exposure (Dieterich et al 2012) as well as on the total load of heat stress over a given period of time Scheil et al 2011).…”
Section: Introductionmentioning
confidence: 99%